Soil organic nitrogen content and composition in different wetland habitat types along the south-east coast of China - Kam Tang (CATENA, 2023)
Soil organic nitrogen (SON) turnover regulates soil nitrogen (N) storage and availability. The coastal mudflats (MFs) in China have undergone drastic transformation due to invasive Spartina alterniflora (SAs) and subsequent reclamation of Spartina marshes to create aquaculture ponds (APs), but the impact on the amounts and compositions of soil nitrogen remains unclear. This study measured the topsoil total nitrogen (STN) and organic nitrogen (SON) compositions in 21 coastal wetlands in southeastern China. Results show that conversion of MFs to SAs increased STN by 38.5%, whereas subsequent conversion to APs decreased it by 16.4%, and the effect was consistent across the broad geographic and climate gradients. Most of the change occurred in the non-acid-hydrolysable fraction of SON, which accounted for 32–42% of STN. Within the acid-hydrolysable fraction, amino acid N, ammonia N and amino sugar N together accounted for about 57%, with the remaining 43% unidentified chemically. Our results suggest that invasion by S. alterniflora was the overwhelming driver to increase bioavailability of nitrogen and related biogeochemical processes in coastal soil, and the effects were partly reversed in subsequent reclamation of Spartina marshes to create aquaculture ponds.